2023
DOI: 10.1182/bloodadvances.2022008159
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating parasite and host-cell factors enabling Babesia infection in sickle red cells under hypoxic/hyperoxic conditions

Abstract: Sickle RBCs (SS) represent a naturally existing host-cell resistance mechanism to hemoparasite infections. Here, we investigate the basis of this resistance using Babesia divergens grown in sickle and sickle trait cells. We found that oxygenation and its corresponding effect on RBC-sickling, frequency of fetal hemoglobin (HbF+) cells, the cellular redox environment and parasite proliferation dynamics, all play a role in supporting or inhibiting Babesia proliferation. To identify cellular determinants that supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 57 publications
2
4
0
Order By: Relevance
“…As parasite growth continued, there was an increased reliance on energy pathways like glycolysis and the TCA cycle to fuel the rapid proliferation, and these changes were reflected in the metabolome of the infected host cells. Additionally, as expected and as previously shown by us using redox dyes ( 32 ), there were significant changes in the redox regulatory pathways in the infected red cells ( Fig. 3f ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As parasite growth continued, there was an increased reliance on energy pathways like glycolysis and the TCA cycle to fuel the rapid proliferation, and these changes were reflected in the metabolome of the infected host cells. Additionally, as expected and as previously shown by us using redox dyes ( 32 ), there were significant changes in the redox regulatory pathways in the infected red cells ( Fig. 3f ).…”
Section: Discussionsupporting
confidence: 90%
“…Strikingly, the key metabolites in the γ-glutamyl cycle and glutathione metabolism were downregulated at D2 (low parasitemia), but as infection progressed, several of these intermediate γ-glutamyl-amino acid metabolites, N -acetylcysteine, S -lactoyl-glutathione, cysteine, glutamate, and 5-oxoproline, were upregulated severalfold, with significant reductions in cysteinyl-glycine and GSH (reduced glutathione). This suggests that with increased proliferation of the parasite, there is an increased reliance on this redox regulatory pathway, as has also been implicated in a recent research study from our laboratory ( 32 ). These findings also largely agree with studies on the metabolomics of Plasmodium falciparum -infected RBCs, where it has been shown that with the progress of infection, these redox pathway intermediates are elevated severalfold ( 29 , 38 ).…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Interestingly, miR-4463 is associated with apoptosis and oxidative stress in endothelial cells. Elevated oxidative stress in the host cells has been linked to intracellular parasite pathogens like Mycobacterium tuberculosis (Chawla et al, 2012) and P. falciparum (Beri et al, 2017;Beri et al, 2019), and our previous work had shown that B. divergensinfected red cells experience disturbed redox homeostasis (Beri et al, 2022). Thus, miRNAs may play a role in causing parasiterelated oxidative stress and could be investigated in future transduction experiments.…”
Section: Microrna Sequencing Analysis Indicates Multiple Human Mirnas...mentioning
confidence: 97%
“…Peak parasitemia was also significantly reduced among RhD+ individuals than RhD- individuals among babesiosis-hospitalized patients. Generally, immune status, age, sickle cell phenotype and asplenia are some of the other known factors that can affect the severity of babesiosis [ 2 , 4 , 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%